Impact of Public Service Motivation on Service Quality in Cambodian Healthcare Settings - Kosal Thay; Sarom Mok; Mengheang Hor; Somuny Som (Universitas Majalengka, 2026)
This study aimed: (1) to examine the level of public service motivation among healthcare providers; (2) to assess the level of service quality in public healthcare settings; and (3) to investigate the relationship between public service motivation and service quality in public healthcare settings in Cambodia. A quantitative research design based on correlational approach was employed. The data were collected from 300 healthcare providers via a structured questionnaire consists of public service motivation (PSM) and service quality (SQ) constructs. Descriptive and inferential statistical method were used to analyze the data. The findings found that the overall PSM was at moderate level (M = 3.49), with self-sacrifice ranked highest among all dimensions. At the same time, SQ was perceived at high level (M = 3.56), with assurance and responsiveness as the top dimensions. Interestingly, the study revealed a positive and statistically significant relationship between PSM and SQ (r = 0.80, p< 0.01), suggesting that higher levels of motivation are associated with better service delivery. The results highlighted the essential role of intrinsic motivation in enhancing healthcare service quality. These findings offer practical insights for advancing healthcare reforms and promoting more responsive and citizen-centered service delivery in Cambodia.